The Influence of the Introduction, Connect, Apply, Reflect, and Extend (ICARE) Learning Model on Cognitive Learning Outcomes in Science and Social Studies (IPAS) in Elementary Schools - Azzahra, Shalimar; Nuraeni, Fitri; Alindra, Afridha Laily (MO.RI Publishing, 2024)
This study addresses the issue of low student learning outcomes attributed to the frequent use of conventional teaching methods by educators in elementary schools. The Introduction, Connect, Apply, Reflect, and Extend (ICARE) learning model is proposed as a potential solution to enhance these outcomes. The purpose of this research is to examine the impact of implementing the ICARE learning model on students' cognitive learning outcomes in science and social studies (IPAS) in elementary schools. Additionally, the study compares the improvement of cognitive outcomes between students taught using the ICARE model and those taught using traditional methods. This quasi-experimental research employs a non-equivalent pretest-posttest control group design. The findings reveal that the application of the ICARE learning model significantly influences cognitive learning outcomes in IPAS subjects, with an effect size of 46.2%. Furthermore, students instructed through the ICARE model demonstrate greater improvement in cognitive learning outcomes compared to those who receive conventional instruction.